Proceedings of 6th International Fuzzy Systems Conference
DOI: 10.1109/fuzzy.1997.622838
|View full text |Cite
|
Sign up to set email alerts
|

Implementation issues in the fuzzy c-medians clustering algorithm

Abstract: The fuzzy c-Median (FCMED) clustering algorithm is an altemating optimization (AO) method of solving the .fuuy c-Means (FCM) clustering algorithm using the 11 -norm. This algorithm is more resistant to outliers than the FCM-A0 algorithm using the P2-norm.The robustness of the FCMED does not come free, since the -fuzzy median is the cluster-centering statistic and exact evaluation of the fuzzy median usually involves ordering the sample values. The eflciency of calculating the fuzzy median is an important imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Kersten suggested that city block distance (or norm) could improve the robustness of FCM to outliers [163]. Furthermore, Hathaway, Bezdek, and Hu extended FCM to a more universal case by using Minkowski distance (or norm, ) and seminorm for the models that operate either directly on the data objects or indirectly on the dissimilarity measures [130].…”
Section: )mentioning
confidence: 99%
“…Kersten suggested that city block distance (or norm) could improve the robustness of FCM to outliers [163]. Furthermore, Hathaway, Bezdek, and Hu extended FCM to a more universal case by using Minkowski distance (or norm, ) and seminorm for the models that operate either directly on the data objects or indirectly on the dissimilarity measures [130].…”
Section: )mentioning
confidence: 99%
“…This occurs due to the fact that d ij = ||x j − c i || 2 2 which can lead to cluster prototypes being pulled away from the main distribution of the cluster. Kersten [22] and Miyamoto and Agusta [27] independently proposed replacing ||x j − c i || L p norm FCM clustering [19] is based on this observation. The objective function employed is hence formulated as…”
Section: P Norm Fcm Clusteringmentioning
confidence: 98%
“…However, if α has not been properly defined, this can result in a even slower convergence of clustering. To avoid this, Equation 22 can be modified as…”
Section: Rcfcm and S-fcm Clusteringmentioning
confidence: 99%
“…However, the resulting FCM cluster representatives (prototypes) are the linear statistics of data points which are known to be vulnerable to outliers [7]. Hence, in the presented approach we applied the robust partitioning method based on the fuzzy median (Fuzzy c-Medians, FCMed) [8].…”
Section: Estimation Of Amplitude Threshold With Median Fuzzy Clusteringmentioning
confidence: 99%
“…To increase the efficiency of median calculation we applied the algorithm, defining the prototypes as a root of the derivative of fuzzy median functional [8] which can be found with bisection method.…”
Section: Estimation Of Amplitude Threshold With Median Fuzzy Clusteringmentioning
confidence: 99%